Simply adding oral nutritional supplementation to haemodialysis patients may not be enough: a real-life prospective interventional study - Ocepek, Andreja; Ekart, Robert; Povalej Bržan, Petra; Bevc, Sebastjan (Frontiers in Nutrition, 2023)
Protein energy wasting (PEW) is a common and serious co-morbidity in haemodialysis (HD) patients. Its importance as a prognostic factor has been increasingly recognised during past decades. Much effort has been invested in the improvement of nutritional status and amelioration of consequences through different therapeutic approaches, either intradialytic parenteral nutrition or more commonly oral nutritional supplementation. In the article, we present the results of a prospective study in HD patients after 12 months of therapeutic intervention with oral nutritional supplements (ONS). 92 HD adult patients were enrolled in the study after three months wash-out period. At baseline nutritional status was assessed using composite scores, laboratory markers, bioelectrical impedance analysis and hand-grip strength test. Patients recognised as undernourished or at high risk for undernutrition received renal-specific commercially available ONS on HD day in addition to their regular diet. After 12 months, the effect of ONS on surrogate markers of undernutrition, serum albumin level, phase angle and hand-grip strength was analysed in 71 surviving patients. After 12 months data for 71 patients, 39 (54.9%) male, 62.4±12.9 years, median haemodialysis vintage 53.3 (IQR 27.5-92.8) months, was available. Patients were divided into three groups: in group A were patients with normal nutritional status at baseline not necessitating ONS; in group B were patients who received ONS; and in group C were patients entitled to receive but refused to take ONS. Baseline results showed statistically significant differences between groups in serum albumin levels and phase angle but not hand-grip strength. Differences between groups remained statistically significant at month 12; we did not find any statistically significant positive changes within groups indicating no positive effect of intervention with ONS. In a prospectively designed interventional single-centre study, we did not find a statistically significant change of surrogate markers of PEW in our cohort of HD patients receiving ONS for 12 months. Since PEW is an independent risk factor influencing the survival of HD patients, efforts should be directed towards a timely and comprehensive nutritional approach, including intensive, personalised dietary counselling, increase in protein and energy intake and advocating tight control of nutritional status during HD treatment.